On the Influence of Kawakami's Marxist Historical Materialism under the Background of Intelligent Network Technology. (26th July 2022) - Han, Wenli; Xu, Sun; Xiong, Ma; De, Li; Neely, Leo
Abstract : In order to study the influence of the dissemination of Kawakami's Marxist historical materialism under the background of intelligent network technology, the research on the influence of the dissemination of Kawakami's Marxist historical materialism under the background of integrated media technology is discussed, through the overall effect and comprehensive performance of the influence of integrated media technology under the background of ordinary network technology and intelligent network technology on the dissemination of Kawakami's Marxist historical materialism, compared with the coupling degree, and has statistical significance. It is obvious that the analysis and research using intelligent network technology are better than the previous ordinary network technology. At the same time, the propagation speed of intelligent network technology is faster, more convenient, more comprehensive, and more secure, achieving the real era of Internet big data information intelligence. Through the integration of media technology under the background of intelligent network technology, the spread influence of Kawakami's Marxist historical materialism has increased rapidly. It has broadened the path of the spread of Marxist theory, accelerated the spread of Marxism, and had a certain impact on the spread of Marxist theory, becoming more popular and convenient, so that people all over the world can have a deeper understanding of their ideological theory, thus changing people's world outlook and values and driving the development of national economy, culture, and humanistic thought.